Research-Based Practice Guide to Address Gang Violence, 9 U.S. states, 2018-2021 - Jannetta, Jesse ([Verlag nicht ermittelbar], 2022)
The project focused specifically on strategies and approaches explicitly intended to reduce gun-related violence committed by young people between the ages of 10 and 25 who may also be associated with gangs/groups, including interventions that solely or primarily serve youth. The study team did not focus on all strategies designed to reduce youth violence, nor on gang prevention and intervention efforts not expressly intended to reduce gun violence and homicide. Based on this framing, the study team focused on interventions that are immediate responses to an acute problem, rather than those that address risk factors associated with violence broadly. This work drew on three main models of interventions: Spergel Model of Gang Intervention and Suppression ("Spergel")/Office of Juvenile Justice and Delinquency Prevention (OJJDP) Comprehensive Gang Model (CGM) intervention models, focused deterrence models, and public health models. Both the review of literature and scan of practice include some interventions that do not fit into any of these models.The review of literature included identification and synthesis of research on the implementation and impact of relevant violence prevention, reduction, and control strategies. The literature review only included interventions that have published research about their efficacy. The scan of practice identified 14 interventions and conducted 13 virtual site visits including interviews and observations. Site selection was based on criteria and with input from a group of subject-matter experts, National Institute of Justice (NIJ), and OJJDP. The scan of practice was not a comprehensive scan and did not include a representative sample by type or location of intervention.